130k views
3 votes
Help?,?,?,?.!.??.?.?.?.?.?.

Help?,?,?,?.!.??.?.?.?.?.?.-example-1

1 Answer

4 votes

Answer:

Explanation:

b(a + 1) + a = b*a + b + a = ab + b + a

1) b(2a +1 ) = b*2a + b*1 = 2ab + b Not equivalent.

2)a + (a +1)*b = a + ab+ b Equivalent

3) (a +1)(b+ a) = a*(b +a) + 1*(b+a) = ab+ a² +b + a Not equivalent.

4) (a + 1)b + a = ab+ b + a Equivalent

5) a + b(a+1) = a +ab + b Equivalent

6) a + (a +1) + b = a + a + 1 + b = 2a + 1 +b Not equivalent.

7) a(b +1) + b = ab + a + b Equivalent

User Khaled Qasem
by
6.2k points